2003
DOI: 10.2355/isijinternational.43.175
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Particle Free Space on Hearth Drainage Efficiency.

Abstract: This paper presents an experimental and numerical study of the two-phase flow in a particle packed bed, under conditions related to a blast furnace hearth. In these models, drainage velocities, slag ratio, tapping time, and maximum slag level in hearth are studied. The coke free space formed at tap hole level forms a circumference slag flow and significantly improves the hearth drainage efficiency. When the coke free space surround a part of packed bed, the effect is in proportion to the surrounded packed bed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 2 publications
2
49
0
Order By: Relevance
“…Nouchi et al examined the effect of particle free space on hearth drainage efficiency by using immiscible two different density fluids. 6) They reported the coke free zone in front of the taphole drastically changed the residual slag volume in the hearth. However, the effect of other in-furnace conditions for examples, slag viscosity, iron and slag density has not been examined because immiscible appropriate liquids for their experiment are limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nouchi et al examined the effect of particle free space on hearth drainage efficiency by using immiscible two different density fluids. 6) They reported the coke free zone in front of the taphole drastically changed the residual slag volume in the hearth. However, the effect of other in-furnace conditions for examples, slag viscosity, iron and slag density has not been examined because immiscible appropriate liquids for their experiment are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, the slag flow behavior should be understood precisely. [1][2][3][4][5][6][7] Fukutake and Okabe proposed 'flow out coefficient', F L , and they concluded that their correlation can be used to estimate residual slag volume in a blast furnace. [1][2][3] At the same time, the effect of the iron phase below the taphole was not considered.…”
Section: Introductionmentioning
confidence: 99%
“…An efficient and strictly controlled tapping is necessary for guaranteeing a stable operation and high productivity of the BF. Many recent investigations [1][2][3][4][5][6][7][8][9] on this subject have revealed that the pressure drop caused by fluid flow through the deadman in the hearth is a significant factor governing hearth drainage. However, due to the hostile environment, the possibilities to directly measure internal variables are practically nonexistent.…”
Section: Introductionmentioning
confidence: 99%
“…the formation of coke free zone, affects the liquid drainage. 34,35,44,45) The flow of particles in the hearth is mainly driven by the downward gravitational and upward buoyancy forces, and hence strongly affected by the level of liquid and the position of discharging hole due to the upward buoyancy forces. 34) An attempt was recently made by Nouchi et al 35) to simulate the solid flow in BF hearth and reveal the formation mechanisms of dead zone.…”
Section: Solid Flow In the Hearthmentioning
confidence: 99%